Worker Safety Monitoring System in the Telecommunications Industry Based on the Internet of Things - Rusdi, Muhammad; Yuvina; Hulu, Fitria Nova; Daulay, M. Sukri Habibi; Wirasari, Riza Ria (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Occupational Health and Safety (OHS) is a protective measure aimed at ensuring workers remain safe and healthy while performing their duties in the workplace. OHS planning aims to create a comprehensive occupational safety and health management system within the workers' scope. The telecommunications industry is one of the sectors that implements OHS principles. Workers in the telecommunications industry face higher occupational accident risks due to direct interaction with heavy objects, sharp materials, electricity, and working at heights. This research aims to design a smart helmet prototype integrated with the Internet of Things (IoT) to monitor safety for telecommunications industry workers. The system to be developed consists of a PPE (Personal Protective Equipment) helmet equipped with an IoT system. The PPE helmet is integrated with an ESP32 microcontroller, LDR sensor, gyroscope sensor, and GPS module, utilizing wireless transmission media connected to an IoT Cloud server that links the microcontroller system with users. The designed system can monitor whether workers are wearing helmets properly, and monitoring results are transmitted in real-time via Telegram, enabling early warnings if potential hazards threaten workers. The research will be tested at PT. Mitra Globalindo Nusantara, a company engaged in fiber optic telecommunications construction. From the discussion results, it was found that the IoT-based safety monitoring system for telecommunications industry workers using LDR sensors, gyroscope sensors, GPS modules, and Telegram monitoring was successfully designed and implemented as a well-functioning prototype. The Telegram application successfully sends notifications regarding the worker's safety condition, including alerts when the helmet is not worn, tilted, or has fallen. The response time for sending and receiving notifications via Telegram was recorded between 1.5 to 2.2 seconds, which is considered acceptable for real-time monitoring systems.